CHALLENGES OF GOVERNING GROUNDWATER IN U.S. WESTERN STATES - Schlager E. (My University, 2006)
Over the last several decades, water users in the western United States have increasingly turned to groundwater resources to support economic development, but few institutional arrangements were in place to govern groundwater use. Over time, numerous groundwater problems have emerged. Two closely related explanations for this are explored. Surface water sources were the first to be developed, and institutional arrangements to allocate surface water were the first to be devised. These arrangements are not particularly well suited for governing groundwater. Furthermore, the physical differences between rivers and aquifers lead to differences in the development of each type of water, and in production and organization costs. Groundwater development involves low upfront production costs, which individual water users can cover. Once groundwater users have individually invested in productive activities problems emerge, such as declining water tables. Thus, unlike surface water users, groundwater users are faced with devising institutional arrangements to coordinate their water uses after they have invested in and developed productive economic activities. Most western states regulate pumping, although groundwater users, in general, resist pumping limits. The discussion concludes with proposals for modifying the prior appropriation doctrine to better accommodate the active management of groundwater basins for long-term sustainability.
Keywords: LEGISLATION; GROUNDWATER DEVELOPMENT; GROUNDWATER/SURFACE-WATER RELATIONS; WESTERN UNITED STATES